2020
DOI: 10.1155/2020/6401969
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Functional Changes in Peripheral Blood Natural Killer Cells in Crohn Disease Patients

Abstract: We investigated activation status, cytotoxic potential, and gut homing ability of the peripheral blood Natural Killer (NK) cells in Crohn disease (CD) patients. For this purpose, we compared the expression of different activating and inhibitory receptors (KIR and non-KIR) and integrins on NK cells as well as their recent degranulation history between the patients and age-matched healthy controls. The study was conducted using freshly obtained peripheral blood samples from the study participants. Multiple color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 76 publications
2
7
0
Order By: Relevance
“…The same was observed in the villus IEC/IEL ratio, where EXP-2, EXP-3 and POS CONT showed significant lower ratios than NEG CONT and EXP-1. This IEC/IEL ratio reduction occurs due to increased proliferation of leucocytes in the lamina propria and massive infiltration in epithelium as already observed [69][70][71] .…”
Section: Discussionsupporting
confidence: 70%
“…The same was observed in the villus IEC/IEL ratio, where EXP-2, EXP-3 and POS CONT showed significant lower ratios than NEG CONT and EXP-1. This IEC/IEL ratio reduction occurs due to increased proliferation of leucocytes in the lamina propria and massive infiltration in epithelium as already observed [69][70][71] .…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, they demonstrated that blood NK cells were activated and generally more poised to migrate to the gut in treatment-naïve CD patients as compared with control subjects. 15 As we observed reduced numbers of NK cells, independent of active inflammation (albeit in non-treatment-naïve UC and CD patients) this might suggest an increase in NK cell egress to the gut. NK cells may play a proinflammatory role, being a primary source of IFNg, important in the skewing toward Th1 response.…”
Section: Discussionmentioning
confidence: 53%
“…Our results are generally consistent with previous reports implicating NK cells in IBD. While Samarani et al 15 demonstrated increased levels of blood NK cells in treatment-naïve CD patients relative to control subjects, they did observe a reduction in specific blood NK subsets such as CD56 bright CD16 low . Furthermore, they demonstrated that blood NK cells were activated and generally more poised to migrate to the gut in treatment-naïve CD patients as compared with control subjects.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…There are three NCRs expressed on human NK cells: NCR1 (NKp46/CD335), NCR2 (NKp44/CD336) and NCR3 (NKp30/CD337). While NCR1 and NCR3 are constitutively expressed on resting NK cells [ 20 , 21 , 22 ], NCR2 is only induced upon NK cell activation [ 23 ].…”
Section: Nk Cell-activating Receptors and Their Ligandsmentioning
confidence: 99%